MESSAGE ACCEPTANCE OF NGAJI FILSAFAT PREACHING THROUGH INSTAGRAM - Bayujati Prakoso (Mediakom, 2020)
This study aimed to understand the impact of message acceptance of Ngaji Filsafat preaching through Instagram using the Albert Bandura Social Learning Theory. In achieving the goal, this study used a qualitative approach with the case study method. Data sources of this study were from interviews on 13 informants and documentation. The study result shows that Ngaji Filsafat preaching through Instagram is effective in motivating hijra for the better, such as improving religiosity understanding, providing life values motivation, motivating to continue to improve and reflect oneself, improving knowledge insight, and triggering oneself to create change movements. These behaviors are inherent with environmental factors, knowledge (personal), and informants’ behavior. It is consistent with Albert Bandura’s triadic reciprocal.